The Opacity of Kidney in Nephrogram Phase with Different Urea and Creatinine levels in Patients Who Undergoing Intravenous Pyelography Examination - Sudiyono Sudiyono; Dwi Rochmayanti; Asri Indah Aryani (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
The examination of intravenous pyelography (IVP) is one of the tests carried out with the aim to examine abnormalities of urinary tract anatomy and physiology. The opacity of urinary tract anatomy and function of the kidney, especially on an X-ray, is influenced by serum urea and creatinine levels of the patients prior to conducting the IVP examination. The study was an observational survey with retrospective approach. Purpose of this study was to describe the opacity of kidney picture in Nephrogram phase with different urea and creatinine levels. Urea and creatinine data were obtained from medical records of patients who underwent radiological examinations in Dr. Moewardi Hospital in 2013. The nephrogram phase imaging picture was taken from the document of Computed Radiography. The study sample was 41 patients. Data of overview kidney opacity in nephrogram phase were analyzed with Matlab software to get the value at the point calyces Pixel kidney (ROI). Research results revealed that 32 p atients (78%) of 41 patients had laboratory results of urea levels higher than normal (8-25 mg/100 ml) and 34 patients (83%) had normal creatinine levels (0.6 to 1.2 mg/ 100 ml). The results of test matlab found that opacity kidney picture nephrogram phase in patients with urea level higher than normal had a decrease of Pixel value (65220 pix.value) when compared to patients with normal urea levels (65231 pix. values ). Patients with creatinine above 1.2 mg/ 100 ml had a higher Pixel value (65239 pix.value), comparing to patients with normal creatinine levels (65219 pix.value). Further research is expected to gain more understanding. It is recommended that patients' levels of urea and creatinine should be checked in 48-72 hours before the time of IVP test, and interventions to decrease these levels should be implemented before conducting the test.